ANALYSIS AND GENERALIZATION OF PSYCHOLOGICAL TRAINING OF ATHLETES (Physical Culture and Sport: Scientific Perspective, 2022)
Psychological training is one of the leading forms of psychological support, covering the period from the moment a child enters a sport and some time after the athlete finishes regular sports. The importance of this type of training is due to the focus on the formation of those qualities and properties of the athlete's psyche that ensure high performance of his activities.The article analyzes and summarizes the problem of psychological training of athletes. The essence of the general and special psychological training of athletes has been defined and specified, a number of defining features of the psychological training of athletes regarding the improvement of personality traits important for sports have been determined.In general, psychological training represents the process of development and improvement of significant manifestations of the athlete's psyche, which meet the requirements of training and competitive activities. Psychological training is aimed at the formation of the personality of the mental qualities necessary for sports activities, professionally important knowledge, abilities, skills and the achievement of their stability, which will ensure the possibility of solving the tasks during the competition.The main task of psychological training is the formation of a sports character, which is created under the influence of external factors, as well as under the influence of internal self-organization, that is, in the process of self-education of an athlete.Psychological training is a complex and long-term process that includes general and special psychological training. Each of these types is aimed at preparing for a certain type of activity in sports, which determines their specific purpose, content and specificity of the organization.
Keywords: psychic and psychological preparation of the athlete; physical exercises; psychological strategy